Goiter in a Patient with Pulmonary Arterial Hypertension Treated with Epoprostenol - Abughazaleh, Shaadi (Case Rep Pulmonol, 2020)
A 35-year-old female with pulmonary arterial hypertension (PAH) who presented with complaints of progressively worsening dysphagia, facial swelling, and shortness of breath, was found to have a large goiter. In patients treated with epoprostenol for long periods of time, thyroid disease is common. Most cases of thyroid disease describe thyrotoxicosis and hyperthyroid statues, but our case was a patient on long term IV epoprostenol presenting with a superior vena cava-syndrome (SVC) like appearance and airway compromise found to have a goiter incidentally during workup.